Intervenções do Ministro da Saúde Alexandre Padilha na 79ª Assembleia Mundial da Saúde (Cadernos Fiocruz de Saúde Global e Diplomacia da Saúde, 2026)
GENERAL DEBATE – PLENARY FIRST ANNIVERSARY OF THE GLOBAL COALTION FOR LOCAL AND REGIONAL PRODUCTION, INNOVATION AND EQUITABLE ACCESSTHE BELÉM HEALTH ACTION PLAN: FROM COP30 TO COP31 – PROMOTING CONTINUITY IN CLIMATE AND HEALTH ACTION